Clinical placements in private practice for physiotherapy students are perceived as safe and beneficial for students, private practices and universities: a national mixed-methods study - Peiris, C.L.; Reubenson, Alan; Dunwoodie, R.; Lawton, V.; Francis-Cracknell, A.; Wells, C. (2022)
Question: What are the extent and characteristics of clinical placements in private practice for physiotherapy students? What do university clinical education managers perceive to be the benefits, risks, barriers and enablers of clinical placements in private practice for physiotherapy students? What training and support are available for private practitioners?